Binding profile of a mixed-ligand silver(I) complex with DNA and Topoisomerase I. (April 2023) - Movahedi, Elaheh; Razmazma, Hafez; Rezvani, Alireza; Ebrahimi, Ali
Abstract: A new mixed-ligand Ag(I) complex, [Ag(daf)(phen)]NO3 (daf = 4, 5-diazafluoren-9-one and dian = N-(4, 5-diazafluoren-9-ylidene)aniline), was synthesized. The elemental analysis, FTIR, 1 HNMR, UV–Vis spectroscopy, cyclic voltammetry, and DFT (Density Functional Theory) geometry optimization method were applied in order to predict the Ag(I) complex structure which concluded to a distorted tetrahedral N4 coordination around the Ag(I) center. A detailed in silico analysis of the bioaffinity of the complex to DNA and human DNA-Topoisomerase I was conducted using molecular docking simulations and ONIOM (Our own N-layered Integrated molecular Orbital and molecular Mechanics) techniques. In this overall scenario, the results suggest the dominance of π-π stacking interactions of the heteroaromatic ligands in the intercalating pocket of DNA and the active site of the enzyme and the rational correlation between being a good intercalator and a potent Topoisomerase I inhibitor. In vitro DNA-binding experiments by spectrophotometric, spectroﬂuorometric, Voltammetric, and viscometric techniques at physiological pH also confirmed the computational results. The complex inhibited MCF-7 cell growth in a dose-dependent manner while being nontoxic on HUVEC normal cells. Graphical Abstract: ga1 Highlights: A new bis-chelated distorted tetrahedral silver(I) complex was synthesized. The complex was highly cytotoxic against the MCF-7 cells and nontoxic on HUVEC. Dual DNA/Topoisomerase I interaction was studied by molecular docking and ONIOM. The complex-DNA intercalation was studied by in vitro biophysical methods.